2013
DOI: 10.3390/ijms140714996
|View full text |Cite
|
Sign up to set email alerts
|

Induced Production of 1-Methoxy-indol-3-ylmethyl Glucosinolate by Jasmonic Acid and Methyl Jasmonate in Sprouts and Leaves of Pak Choi (Brassica rapa ssp. chinensis)

Abstract: Pak choi plants (Brassica rapa ssp. chinensis) were treated with different signaling molecules methyl jasmonate, jasmonic acid, linolenic acid, and methyl salicylate and were analyzed for specific changes in their glucosinolate profile. Glucosinolate levels were quantified using HPLC-DAD-UV, with focus on induction of indole glucosinolates and special emphasis on 1-methoxy-indol-3-ylmethyl glucosinolate. Furthermore, the effects of the different signaling molecules on indole glucosinolate accumulation were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 49 publications
2
54
1
1
Order By: Relevance
“…Observed differences possibly indicate a species-specific interaction of bacterial treatment, plant age, and induction of glucosinolate biosynthesis. In contrast, the absence of altered levels of indolic glucosinolates supports findings from the Arabidopsis-K. radicincitans system that jasmonic acid signaling is not involved, since indolic glucosinolates were found to be induced by jasmonate (Brader et al 2001;Wiesner et al 2013). It seems that a plant's response to K. radicincitans is species specific, and whether it is a wild plant or cultivar appears to have a minor influence.…”
Section: Glucosinolate Profile In K Radicincitans-inoculated Radishsupporting
confidence: 69%
See 1 more Smart Citation
“…Observed differences possibly indicate a species-specific interaction of bacterial treatment, plant age, and induction of glucosinolate biosynthesis. In contrast, the absence of altered levels of indolic glucosinolates supports findings from the Arabidopsis-K. radicincitans system that jasmonic acid signaling is not involved, since indolic glucosinolates were found to be induced by jasmonate (Brader et al 2001;Wiesner et al 2013). It seems that a plant's response to K. radicincitans is species specific, and whether it is a wild plant or cultivar appears to have a minor influence.…”
Section: Glucosinolate Profile In K Radicincitans-inoculated Radishsupporting
confidence: 69%
“…Desulfoglucosinolate extraction and analysis were carried out as described recently (Wiesner et al 2013). In short, 20-mg aliquots of leaf and tuber tissue were extracted with 750 μl 70 % (v/v) hot methanol and 100 μl of 0.1 mM 2-propenyl glucosinolate internal standard (BCR-367R; Community Bureau of Reference, Brussels) for 10 min in boiling water.…”
Section: Desulfoglucosinolate Extraction and Analysismentioning
confidence: 99%
“…Among several elicitors, MeJA was found to be most effective for inducing the biosynthesis of IGS, particularly the neoGBC (Smetanska et al, 2007;Wiesner et al, 2013). These findings were confirmed in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Exogenous JA application dramatically increased the level of IGS, resulting in the enhanced resistance of Arabidopsis to both phloem-feeding and chewing insects (Mikkelsen et al, 2003;Mewis et al, 2005). Upon MeJA treatment, neoGBC significantly accumulated in the leaves of Brassica crops such as pak choi (Wiesner et al, 2013), cabbage (Fritz et al, 2010), oilseed rape (Brader Loivamäki et al, 2004), broccoli (Pérez-Balibrea et al, 2011), Chinese kale (Sun et al, 2012), and turnip (Smetanska et al, 2007). SA treatment on Brassica plants increased the accumulation of aromatic, indole, and aliphatic GSs, though accumulation profiles of the individual components vary greatly depending on the plants (Kiddle et al, 1994;Mikkelsen et al, 2003;Smetanska et al, 2007;Pérez-Balibrea et al, 2011;Sun et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that plant signaling molecules such as methyl jasmonate, salicylic acid and glucose as well as mechanical injury could alter glucosinolates levels in Arabidopsis and Brassica species (Bodnaryk, 1992;Brader et al, 2001;Doughty et al, 1991;Guo et al, 2013;Kiddle et al, 1994;Miao et al, 2013;Mikkelsen et al, 2003). The effects of these molecules may vary from one crop to another and would depend on the type of glucosinolates present and the ontogenetic differences of plant species (Baenas et al, 2014;Wiesner et al, 2013).…”
Section: Introductionmentioning
confidence: 96%